"Lift Big–Get Big": The Impact of Images of Hyper-Muscular Bodies and Training Information. Issue 3 (3rd July 2021) - Martino, Elio; Fisher, James P.; Wink, Brian; Smith, Dave; Steele, James
ABSTRACT: Purpose : It has been suggested that the media influence beliefs regarding ideal body appearance and drive for muscularity whilst also offering recommendations for achieving this; most commonly heavy load free weight resistance training (RT). However, evidence for media effects are inconsistent in the literature. This study investigated this "lift big–get big" culture and effects of imagery on males' beliefs regarding RT. Method : An online survey was conducted with male participants ( N = 110) randomized to different images (hyper-muscular/lean/control) and RT information ("lift big–get big"/"evidence based RT"/control). Results : Descriptive data suggested belief in necessity of heavy loads and free weights was pervasive. There was a small significant effect of condition for multivariate analysis of beliefs regarding RT. Univariate analyses showed significant effects of condition regarding the importance of free weights and heavy loads for strength, and free weights for hypertrophy. Small to moderate effects were found comparing "evidence-based RT" with a hyper-muscular physique to "lift big–get big" conditions with both hyper-muscular and lean physiques, the latter more likely to agree free weights and heavy loads are necessary for strength. A small effect was found comparing "lift big–get big" conditions with both hyper-muscular and lean physiques and the control condition, the former more likely to agree free weights are necessary for hypertrophy. Conclusions : Although hyper-muscular bodies alone did not influence RT beliefs, new information, i.e., "evidence-based RT" combined with a hyper-muscular physique had a small effect. The "lift big–get big" culture is perhaps pervasive enough that most conditions merely reinforced existing beliefs.